Identifying Missed Care in Pediatric Nursing: A Literature Review - Ekawaty, Fadliyana; Mulyani, Sri; Asyhar, Rayandra (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Missed nursing care, which refers to necessary patient care that is omitted or delayed, is a significant concern in pediatric nursing. This literature review aimed to describe missed nursing care in pediatrics, identify the most commonly missed nursing care categories, and summarize the underlying reasons. Method: A comprehensive search was conducted in PubMed, Embase, CINAHL, and Scopus databases without time limits. Quantitative studies reporting on missed nursing care categories, reasons, and associated factors in pediatric settings, published in English with full text available, were included. Seven articles were selected for analysis. Result: The results showed that missed nursing care was influenced by workload, work environment, and staffing levels. Higher patient-to-nurse ratios significantly increased the incidence of missed care. Better work environments correlated with fewer missed nursing activities, but frequent interruptions and unexpected patient volume surges remained major issues. Frequently missed activities included oral care, routine bathing, and adherence to infection protocols. Nurse characteristics such as age, education level, and working hours also impacted missed care and job satisfaction. Addressing missed nursing care requires strategic staffing, improved work environments, targeted interventions, and ongoing education to enhance care quality. Conclusion: This review highlights the complexity of missed nursing care and its dependence on various factors, including workload, work environment, and nurse characteristics. Developing and validating pediatric-specific assessment tools and studying factors such as workload, staff training, and work environment are crucial for addressing missed nursing care in this setting.